Effects of low-level water addition on spray, combustion and emission characteristics of a medium speed diesel engine fueled with biodiesel fuel. (1st March 2019) - Zhang, Zhiqing; E, Jiaqiang; Chen, Jingwei; Zhu, Hao; Zhao, Xiaohuan; Han, Dandan; Zuo, Wei; Peng, Qingguo; Gong, Jinke; Yin, Zibin
Graphical abstract: Highlights: Different low-level of water-biodiesel emulsion fuels are employed in this work. Effects of water additive rate on spray, combustion and emission characteristics are investigated. A computational modeling is developed by the chemical kinetics mechanism. Water additive and the kinetic viscosity of biodiesel fuel play very important roles. Abstract: In this work, the low water-level water-biodiesel emulsion (WBE) fuels (2, 4 and 6 wt%) and pure biodiesel fuel were used to investigate the effects of water addition on spray, combustion and emission characteristics of a medium speed diesel engine in terms of cylinder pressure, cylinder temperature, heat release rate, brake power, brake thermal efficiency, brake specific fuel consumption, NOx, soot, CO and CO2 emissions. The corresponding three-dimensional CFD model was performed by AVL-Fire coupled CHEMKIN II code, and an improved chemical kinetics mechanism containing 475 reactions and 134 species was developed to simulate the fuel spray process and combustion process since it contained methyl linolenate, methyl linoleate, methyl oleate, methyl stearate, methyl palmitate, a majority component in most biodiesel, thus improved the accuracy of simulation. The result obtained showed that the water addition in fuel played an important role in fuel spray process and fuel combustion process. The fuel-air mixing was improved due to the micro-explosion. More specifically, the findings revealed that low-level water addition in biodiesel fuel could reduce NOx, CO and CO2 emissions. The optimal water addition level in terms of diesel engine emission and performance parameters was found at 4 wt% among WBE fuels. In particular, the NOx, CO and CO2 emissions were reduced respectively, at maximum speed of 1000 rpm. Thus, the relationship between water addition rate and combustion and emission characteristics is not straightforward, the balance between water addition and fuel is very important.